2014
DOI: 10.4236/aim.2014.416130
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Traditional Susceptibility Testing for MRSA with the PCR Approach

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a multi-drug resistant pathogen, which is responsible for increasing cases of serious diseases, including life-threatening diseases and nosocomial and community-acquired infections. Laboratory identification of MRSA is crucial and essential both for initiation of appropriate antimicrobial therapies and for effective infection control strategies that are designed to limit the spread of MRSA. In spite of the availability of commercial kits for MRSA detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…2 These trends have directed the focus towards multiplexed lab-on-a-chip devices, where several nucleic acid targets can be amplified and characterized in one sealed reaction unit in a separation-free manner. 3 Integrated multiplexed processing and handling of small samples and reagent volumes in a disposable reaction unit would make the biological analysis more cost-efficient and user friendly and less prone to human error and contamination. Thus far multiplexed nucleic acid assays have mostly been used in gene expression profiling and genotyping applications, but their importance in microbial diagnostics is growing fast 4 especially in pathogen identification and multidrug resistance screening.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 These trends have directed the focus towards multiplexed lab-on-a-chip devices, where several nucleic acid targets can be amplified and characterized in one sealed reaction unit in a separation-free manner. 3 Integrated multiplexed processing and handling of small samples and reagent volumes in a disposable reaction unit would make the biological analysis more cost-efficient and user friendly and less prone to human error and contamination. Thus far multiplexed nucleic acid assays have mostly been used in gene expression profiling and genotyping applications, but their importance in microbial diagnostics is growing fast 4 especially in pathogen identification and multidrug resistance screening.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far multiplexed nucleic acid assays have mostly been used in gene expression profiling and genotyping applications, but their importance in microbial diagnostics is growing fast 4 especially in pathogen identification and multidrug resistance screening. 3 Numerous efforts have been made to develop a relatively fast multiplexed nucleic acid amplification test in a closedtube format for microbial point-of-care testing. The polymerase chain reaction (PCR) is still the most widespread nucleic acid amplification method due to its sensitivity, effectiveness and capacity despite the requirement of special equipment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…qPCR looks at the amplification of DNA, through the generation of thousands to millions of copies of a particular DNA sequence, in real time and can detect down to one microbial cell. 10 This allowed a limit of detection of down to one cell to be achieved. In trials, the research group successfully identified a specific strain of Salmonella (S. enterica), selected from soil samples, and Pseudomonas aeruginosa from samples of water.…”
mentioning
confidence: 99%